2020
DOI: 10.1021/acsomega.0c04658
|View full text |Cite
|
Sign up to set email alerts
|

Superior Crystallization Kinetics Caused by the Remarkable Nucleation Effect of Graphene Oxide in Novel Ternary Biodegradable Polymer Composites

Abstract: In this study, novel ternary composites were prepared, including biodegradable poly(ethylene succinate) (PESu), poly(ethylene glycol) (PEG), and graphene oxide (GO). We have conducted a comprehensive study on whether GO can successfully promote the crystallization behaviors of PESu in the ternary composites. The results of isothermal crystallization demonstrated that with the increase of GO content in the composite (at a fixed PESu/PEG ratio), the Avrami rate constant k gradually increased, indicating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Thus, GO can act a as nucleating agent for the matrix crystallization, resulting in the formation of bigger and more perfect crystals, as previously reported for other nanofillers such as ZnO or boron nitride [ 9 , 25 ]. Indeed, the superior nucleating efficiency of GO has been previously reported for other biodegradable polymeric matrices such as poly (ethylene glycol) (PEG) related to the large nanofiller surface area [ 26 ]. In particular, for the nanocomposite with 2.0 wt% GO, about 25% decrease in the full width at half-maximum (FWHM) of the (110) peak is found, which is indicative of a larger crystallite size since the peak width is inversely proportional to the crystallite size according to the Scherrer formula [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, GO can act a as nucleating agent for the matrix crystallization, resulting in the formation of bigger and more perfect crystals, as previously reported for other nanofillers such as ZnO or boron nitride [ 9 , 25 ]. Indeed, the superior nucleating efficiency of GO has been previously reported for other biodegradable polymeric matrices such as poly (ethylene glycol) (PEG) related to the large nanofiller surface area [ 26 ]. In particular, for the nanocomposite with 2.0 wt% GO, about 25% decrease in the full width at half-maximum (FWHM) of the (110) peak is found, which is indicative of a larger crystallite size since the peak width is inversely proportional to the crystallite size according to the Scherrer formula [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar tendency is also demonstrated in Figure 9 with the F(T)-vs-h-BN content plots. In general, the smaller F(T) value reflects the faster kinetic behavior of crystallization [39]. The relevant results of the Mo analysis for the PESu/h-BN composites demonstrated that the PESu/h-BN composites underwent faster crystallization than PESu.…”
Section: Non-isothermal Crystallization Behaviors Of Pesu/h-bn Compositesmentioning
confidence: 98%
“…Many mathematical models are proposed to clarify the macroscopic evolution of crystallinity for polymers during their crystallization process [ 21 , 22 , 23 , 24 , 25 ]. One of the most frequently used models to describe crystallization kinetics is the Avrami equation with the assumptions of nucleation and geometric growth occurring during the crystallization process of the polymers [ 26 , 27 , 28 , 29 ]. For the analysis of nonisothermal crystallization under linear heating conditions, Jeziorny developed the conventional Avrami equation by adjusting the linear Avrami equation to linear heating conditions by introducing a constant heating rate into the rate constant [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%